Characterization of the gene coding for GDP-mannose dehydrogenase (algD) from Azotobacter vinelandii. - Campos, M (1996)
Azotobacter vinelandii presents a differentiation process leading to the formation of desiccation-resistant cysts. Alginate, the exopolysaccharide produced by this bacterium, has been postulated to have a role in cyst formation. Here, we report the cloning and characterization of the A. vinelandii gene coding for the enzyme GDP-mannose dehydrogenase (algD), which is the key enzyme for alginate synthesis in Pseudomonas aeruginosa. This gene has a high degree of similarity with the algD gene from P. aeruginosa, and similar proteins seem to be involved in algD regulation in both bacteria. We show the existence of two mRNA start sites; one of these sites corresponds to a promoter transcribed by RNA polymerase containing a sigma E subunit. An A. vinelandii algD mutant which is completely impaired in alginate production and which is unable to form desiccation-resistant cells was constructed. The effects of NH4, NO3, and NaCl concentrations on algD transcription for three A. vinelandii strains producing different alginate levels were evaluated. We found a strict correlation between alginate production and algD transcription for the three strains studied; however, the effects on algD transcription under the conditions studied were different for each strain. The nitrogen source regulates algD expression in the wild-type strain.